A global review of the impact of basis risk on the functioning of and demand for index insurance. (June 2018) - Clement, Kristina Yuzva; Wouter Botzen, W.J.; Brouwer, Roy; Aerts, Jeroen C.J.H.
Abstract: Climate change is increasing the risks of weather-related disasters in many regions around the world. This has an adverse socio-economic impact on households, farmers and small businesses. Some strategies for effectively managing climate related disasters include index based insurance products, which are increasingly offered as alternatives to traditional insurance, particularly in low-income countries. However, the uptake of index insurance remains low, which can be partially attributed to the inherent problem of basis risk. This review assesses the problem of basis risk that occurs when insurance payouts depend on an index that is imperfectly related with actual losses experienced by the insurance policyholder. Special attention is paid to the design of the index, quality and sampling data, the estimation of basis risk and its influence on insurance demand, and index-insurance supply. The paper concludes with several policy recommendations including the need for a systematic approach to quantify the magnitude of basis risk, to inform index design with participatory approaches, to offer index insurance through existing risk sharing networks. Moreover, we recommend to improve policyholders access to information about their risk and measures they can take to limit risk, create an enabling environment for a well-functioning insurance market, and lastly to have an integrated approach that incorporates insurance with other mechanisms that reduce basis risk.